UJI INVITRO AKTIVITAS ANTIBAKTERI DARI Lansium domesticum Correa (LANGSAT) - Korompis, Grace; Danes, Vennetia R.; Sumampouw, Oksfriani J. (CHEMISTRY PROGRESS, 2010)
Traditional medicine usage can be a breakthrough for alternative medication with regard of the resistancy ofdiseases-agent to common drugs. Lansium domesticum has been reported containing therapeutic-substancestherefore, has the capacity as a medicine. This research aimed to further elaborate the antibacterial activities ofseeds, fruitshield and bark skin of Lansium domesticum. The in vitro experimental research was conducted,initiated by extract maseration and continued by antibacterial test to bacterial isolation: Salmonella typhii,Escherichia coli, Vibrio cholerae, dan Staphylococcus aureus. Antibacterial activities test has been done bycomparing to several antibiotics and statistically test by ANOVA followed by LSD or BNT test. The study resultshowed that the extract of L. domesticum effectively inhibited the bacterial’s activities. Fitochemistry test of theextract should be conducted to detect the active compound as well as in vivo research for treatment againstbacterial.